Symbolic Communication in Ludruk Art Group Karya Budaya Mojokerto - Evi Nur Fadillah; Chandra Agustin, Dinar Ayu (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2024)
The form of communication is a form of communication through symbols and symbols. However, what are the forms and obstacles encountered when conveying it through the ludruk art performance media. This research is in the realm of field research. The research approach uses a descriptive qualitative approach. Sources of data using secondary and primary data sources. The results of this study explain that the form of symbolic communication in the first LKBM ludruk art group was in the form of arek language as a ludruk player's self-concept in positioning himself and as a ludruk player. Second, a form of symbolic communication through the symbolic movement of the LKBM ludruk art which goes through the mind process of a ludruk player in taking action to draw the meaning of the message content to the audience. Third, a form of symbolic communication through symbolic costumes of LKBM ludruk art with interpretation in the community (society) in interpreting symbols. Fourth, symbolic communication in the form of direct communication between ludruk players and the audience. Through one-way communication (one-way communication) and two-way communication (two-way communication). Keywords: Symbolic Communication, Symbolic Interactionism, Ludruk Art